Insatisfação ou discrepância?: Uma análise das preferências de fecundidade e do comportamento reprodutivo de casais de alta escolaridade em Belo Horizonte/MG - Angelita Alves de Carvalho (2014)
We analyze the process of setting up reproductive preferences intentions and corresponding implementation in the context of below fertility replacement in Brazil and the increasing discrepancy between the number of children desired and actually born. We have two groups of objectives. First, to portray the fertility preferences and satisfaction, highlighting the importance of discrepanct fertility due to lack of children among married women. We identify the relationship between the status of women to have fewer children than those she want and socio - demographic, economic characteristics and gender equi. We used quantitative data from DHS 1996 and 2006. Results indicate that dissatisfaction by lack of children grew considerably over the period, and it is positively correlated with the age at first child and schooling and inversely related to the husbands desire for children. The second set of goals analyzes the setting up of reproductive intentions and desires to have or not (more) children by each spouse and their discrepancy and satisfaction with their actual fertility, identifying the male involvement in the process and gender relationships predominant. A field research based on profile of lack of children women delineated by quantitative data was carried out. Individual interviews with each partner in 31 couples which women had higher education and zero, one and two children in Belo Horizonte, Brazil was done. We identify the complexity of the reproductive decision-making process trhough a deep analysis of discrepancy and satisfaction with the desired number of children by each spouse and speculate about the possible restrictions to implement the reproductive preferences. The results also point out whether current indicators for reproductive preferences are valid.